Design and piloting of a cognitive behavioral group program for anxiety management in university students - Salamanca-Camargo, Yenny; Forero-Mendoza, Ingrid Xiomara (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2021)
Introduction: anxiety has been widely studied, concluding its high prevalence and comorbidity specifically in students since it is one of the most reported problems, as well as its collateral effects; however, studies on group intervention in this type of problems are scarce. Objective: the purpose of this study was to design and pilot a group intervention program for the management of anxiety symptoms in a group of psychology students at a Colombian university. Methodology: the program was designed based on a theoretical and empirical review of different cognitive, behavioral and physiological strategies, as well as content validity by expert judges; while the piloting was carried out with ten participants between 18 and 20 years of age and between second and fourth semester of schooling. Results: significant differences were identified between pre- and post-treatment measures, based on the Anxiety Situations and Responses Inventory, being the most significant change in motor responses.